IMPACT OF PUBLIC ENTERPRISES ON ECONOMIC DEVELOPMENT: A STUDY OF SELECTED STATE-OWNED ENTERPRISES IN EBONYI STATE - NDUKWE, Chinyere; AGHA, Nancy; EDE, Cyril Ede (EBSU Journal of Social Sciences and Humanities, 2023)
The study assessed the impact of public enterprises on economic development with focus on selected state-owned enterprises in Ebonyi State. Specifically, the study examined the extent to which public enterprises have contributed to revenue generation, job creation and improved standard of living in Ebonyi State. New Public Management Theory guided the study. Descriptive survey design was adopted to study 1567 staff of selected enterprises and residents being beneficiaries. The sample size was 319 determined using Taro Yemene’s and Kumar’s sample allocation formulae. Judgmental sampling techniques were adopted. Data were collected from primary and secondary sources. The instrument for data collection was structured questionnaire. Data were analysed using statistical tables, mean and standard deviation. Findings revealed that public enterprises have not significantly enhanced revenue generation in Ebonyi State; public enterprises have not contributed significantly to job creation in Ebonyi State; and public enterprises have not significantly improved standard of living in Ebonyi State. The implication was that public enterprises have not significantly contributed towards economic development of Ebonyi State. Hence, the study recommended that government should adopt new public management strategy to enable state-owned enterprises generate more revenue, there is need for diversification and investment in skill development for job creation, and there is need for adequate provision of basic amenities to improve the standard of living among others.